CULTURAL ASPECTS (FOOD TABOOS) AND MANAGEMENT OF ANAEMIA IN PREGNANCY: A SYSTEMATIC REVIEW - Dewi Hestiani K; Suriyani, Andi (Media Inovasi Pendidikan dan Publikasi, 2023)
Anemia in pregnancy is a significant health issue, especially in developing countries where strong cultural beliefs, including food taboos, are prevalent. Food taboos during pregnancy can restrict the intake of essential nutrients such as iron, leading to a higher risk of anemia. This study aims to systematically review the relationship between food taboos and anemia prevalence in pregnant women across various cultural communities. This systematic review followed the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Literature searches were conducted on several databases, including PubMed, ScienceDirect, SpringerLink, Scopus, and Sage. Articles were screened based on inclusion and exclusion criteria, resulting in the analysis of 7 relevant articles to identify the impact of food taboos on anemia during pregnancy. The analysis revealed that food taboos, particularly concerning the consumption of meat, fish, and green vegetables, significantly contribute to the prevalence of anemia in pregnant women. Several studies also showed that culturally-based interventions effectively improved nutritional intake and reduced the risk of anemia. Food taboos during pregnancy have a significant impact on anemia, and culturally sensitive interventions are crucial for preventing anemia in pregnant women.